MODERATING ROLE OF PSYCHOLOGICAL DISTRESS ON THE RELATIONSHIP BETWEEN SUICIDAL IDEATION AND PSYCHOLOGICAL WELLBEING AMONG PEOPLE WITH PHYSICAL DISABILITIES - Andleeb, Syeda Naila; Ahsan, Sadaf; Zaheer, Sadaf (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the relationship between suicidal ideation and psychological wellbeing and also to investigate the moderating role of psychological distress on the relationship between suicidal ideation and psychological well being.Study Design: Cross-sectional study.Place and Duration of Study: Artificial Limbs Centre, Fauji Foundation Hospital Rawalpindi, from Feb 2016 to Nov 2016.Methodology: The sample comprised of 150 people with physical disabilities. The Modified Scale was used to assess the Suicidal Ideation and The Mental Health Inventory was used to measure psychological wellbeing and psychological distress. Moderation analysis was explored through PROCESS macro.Result: Results showed that suicidal ideation negatively correlated with psychological well-being (r=-0.16, p